2019
DOI: 10.1371/journal.pone.0211561
|View full text |Cite
|
Sign up to set email alerts
|

Does hard mast production affect patterns of cementum annuli formation in premolar teeth of Asian black bears (Ursus thibetanus)?

Abstract: Cementum annuli widths in mammals are is influenced by the nutrition of mammals. Reproductive stress has been is suggested to reduce the width of lead to narrower cementum annuli widths in female Asian black bears (Ursus thibetanus); however, food availability in autumn strongly impacts bear nutrition and likely impacts cementum widths as well. This study aimed to test how cementum annuli widths and the formation of false annuli were influenced by hard mast production. We established two hypotheses: (1) cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ideally, the proportion cementum method (PCM) we describe would be developed using known-age specimens (Figure 2), which can then be used to age specimens of unknown age. Although the proportion cementum model in our example was linear (Figure 2), models for other populations or species may be non-linear depending on how cementum deposition changes with age (e.g., cementum annuli width decreasing with age; Tochigi et al, 2019). If a strong relationship between proportion cementum and age of known-age specimens is identified (e.g., Figure 2), the PCM would likely be a better approach to aging specimens than cementum annuli analysis (CAA).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ideally, the proportion cementum method (PCM) we describe would be developed using known-age specimens (Figure 2), which can then be used to age specimens of unknown age. Although the proportion cementum model in our example was linear (Figure 2), models for other populations or species may be non-linear depending on how cementum deposition changes with age (e.g., cementum annuli width decreasing with age; Tochigi et al, 2019). If a strong relationship between proportion cementum and age of known-age specimens is identified (e.g., Figure 2), the PCM would likely be a better approach to aging specimens than cementum annuli analysis (CAA).…”
Section: Discussionmentioning
confidence: 91%
“…We have demonstrated that the proportion of sectioned tooth area comprised of cementum ("proportion cementum") can predict the age of a mammal species with a high level of accuracy and precision (Figure 2). Although we only examined one species, we think a similar relationship almost certainly exists in other mammal species because cementum is continuously deposited throughout most mammals' lives (Lieberman, 1994), often at relatively similar or predictable rates as mammals age (Grue & Jensen, 1979;Pérez-Barbería et al, 2020;Tochigi et al, 2019). Proportion cementum is an advantageous metric because it assesses cementum deposition in relation to total tooth area.…”
Section: Discussionmentioning
confidence: 95%
“…We used PWI data of bears that were at least five years old to estimate age at first reproduction and reproductive interval. Although female bears are sexually mature and able to reproduce from four years old (Katayama et al 1996; Yamanaka et al 2011b), PWI for four-year-old females can be obtained from the annulus width only between the ages of three and four, because the annulus width from four to five years old is still in the process of formation (Tochigi et al 2019). Therefore, we used the PWI of female bears ≥ five years old.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we used the PWI of female bears ≥ five years old. Previous studies indicated that the PWI was significantly smaller in years when female bears gave birth successfully and raised cubs until at least August (Tochigi et al 2018; Tochigi et al 2019). We used the threshold reported by Tochigi et al (2018); a PWI < 0.25 indicated that the bear probably had a cub or cubs until at least August (i.e., a “cub-year”).…”
Section: Methodsmentioning
confidence: 99%